Técnica de la Reacción en Cadena de la Polimerasa para la identificación de Amebas sp. - Vizuete Parra, Oliver Daniel (2025)
The detection of pathogenic amoebae using the polymerase chain reaction has become a fundamental tool for clinical diagnosis and epidemiological surveillance. The main objective of this literature review was to analyze the technical and methodological aspects of this molecular identification technique to evaluate its diagnostic efficacy and clinical relevance. This descriptive, qualitative, and cross-sectional study conducted a systematic review of 30 scientific articles, focusing on a critical analysis of fundamental parameters. The research was structured around three key methodological components: the composition of the Master Mix, the thermocycler conditions, and the evaluation of agarose gel electrophoresis results. The findings revealed significant variability in the protocols analyzed, particularly in reagent concentrations, temperature parameters, and cycling conditions across different species, although all maintained the basic principles of a conventional polymerase chain reaction. Electrophoresis demonstrated consistent patterns of specific bands under standardized protocols, corroborating the reported high levels of sensitivity and specificity. It was concluded that the success of molecular detection of pathogenic amoebae depends on the correct selection and combination of these methodological components, providing a valuable reference guide for clinical laboratories and epidemiological studies. The results emphasize the need for accurate documentation of these parameters to ensure reproducibility and highlight that the technical specifics of each amoeba species and the amplification stage must be considered.